Redução da morbilidade iatrogénica no local dador de enxerto ósseo. Estudo de alternativas cirúrgicas em modelo ovino - Lavrador, Catarina (2015)
Autogenous cancellous bone graft from the iliac crest and/or the tibial tuberosity is commonly used in the clinics to promote healing of critical-size segmental long bone defects. Bone harvesting is traumatic, causes morbidity of the donor site, and often results in complications. Monocortical bone defects in the ilium resulting from harvesting of bone graft require long time to heal, while bicortical and tricortical defects do not heal for life time. All these promote efforts to develop cancellous bone graft substitutes which might potentially replace autogenous bone graft. Among biomaterials for cancellous bone graft substitutes are bioresorbable polyhydroxyacids and polyurethanes. Polyurethanes are of special interest as they can be synthesized over a broad range of physical and biochemical properties, controllable rates of in vivo degradation and processed into porous scaffolds for tissue engineering and regenerative medicine. Elastomeric polyurethane bone graft substitutes when used to treat bone defects, allow for an intimate contact to be established at the native bone-scaffold interface, which may promote cell migration from bone ends into scaffold and facilitate bone healing. In this study biodegradable elastomeric polyurethane scaffolds were used as cancellous bone graft substitutes to treat critical-size defects in the iliac crest (40 mm X 20 mm) and tibial tuberosity of sheep (15 mm X 15 mm). The polyurethane scaffolds had controlled ratio of the hydrophilic-to-hydrophobic components, the pore size in the range of 80 to 380 μm, the pore-to-volume ratio in the range of 75 to 90%, and were loaded with nanosize hydroxyapatite crystals to promote osteoconductivity. There were four groups of six animals each: Group I (control group) – bone defects left empty; Group II – bone defects covered with a microporous polymeric membrane from poly (L/DL lactide) 80/20; Group III – bone defects filled with polyurethane scaffolds modified with a system of creatine/putrescine and covered with the microporous polymeric membrane from poly (L/DL lactide) 80/20; Group IV bone defects filled with polyurethane scaffolds modified with soy lecithine and covered with the microporous polymeric membrane from poly (L/DL lactide) 80/20. The duration of the experiments was 26 weeks. At this time the animals were euthanized, the bone specimens were harvested and evaluated using computerized tomography, macrorradiography and histomorphometry. Bone specimens for histological evaluation were stained with vital fluorescents stains (calcein green and xylenol orange) and Giemsa-eosin. In group I (control), in both the tibial tuberosity and the iliac crest, in none of the animals there was bone regeneration. This is not astonishing as the defects were of critical-sized. In group II, in both donor sites, the new bone bridged the bone ends in all animals. This clearly indicates that the poly(L/DL-lactide) 80/20 membrane acts as a guide which promotes bone regeneration in the defect covered with membrane (guided bone regeneration GBR). Interestingly, the new bone was also present in the pores of the membrane indicating its osteoconductive potential. Although these results were not statistically significant, they evidently show that the membrane is osteopromotive. In groups III and IV, in which bone defects were implanted with polyurethane scaffolds modified with biologically active compounds, bone regeneration was more efficient then in group II in both the tibial tuberosity and the iliac crest. In groups III and IV there were higher values of: number of osteons per optical field. There were also higher values of: number of osteons per optical field (38,1+8,3 42,7+7,4 and 25,4+12,7 respectively; P<0,05), bone apposition rate (2,7+0,3 2,4+0,1 2,2+0,7 N.S) and bone density of bone regenerate in tibial defect (250,5+143,1 244,6+95,5 10,8+48,0 P<0,05). In the remaining parameters for the tibial tuberosity and iliac crest, we only found values that suggested a favourable tendency to osteoregeneration. There were no statistically significant differences between group III and IV. The results obtained in this study suggest that biodegradable polyurethane cancellous bone graft substitutes modified with biologically active substances may offer an alternative to autogenous cancellous bone graft in the treatment of bone defects. The capacity of these substitutes to facilitate bone regeneration can be promoted by impregnation with specific enrichments. These polyurethane cancellous bone graft substitutes when used to fill donor site defects may significantly reduce their morbidity.